Nodular, non-cirrhotic liver associated with portal hypertension in a patient with rheumatoid arthritis. Issue 12 (December 1974) - Harris, M.; Rash, R. M.; Dymock, I. W.
Abstract : A patient with rheumatoid arthritis developed portal hypertension and died from bleeding oesophageal varices. The liver was small and showed a nodular, non-cirrhotic pattern similar to that described by Blendis et al (1970 and 1974) in association with Felty's syndrome. This appears to be the first report of a patient with this liver lesion associated with rheumatoid arthritis in the absence of Felty's syndrome. The liver lesions described here are compared with partial nodular transformation and nodular regenerative hyperplasia; in spite of some differences it is not proven that these are distinct entities and further study is required to settle this question.